Over Confidence, Mental Accounting, and Loss Aversion In Investment Decision - Rohmad Fuad Armansyah (JAFFA, 2021)
The psychology related to investment cannot be ignored by individuals who want to get investment returns. Investment decisions are the most important decisions in decision making. This investment decision is a policy carried out by investors to invest in one or more assets to get more profits in the future. Overconfidence investors prefer higher risk returns to be more important than those overestimated in terms of their knowledge and lower than expected. Mental accounting considers the costs and benefits of loss avoidance decisions made by investors to protect themselves against losses. This study discusses financial problems related to community investment decisions, special investments in real assets and financial assets. The data used are 250 respondents' data on Indonesian investors who invest in Indonesian capital markets. The results showed that overconfidence and mental accounting significantly affected investors' investment decisions in the Indonesian capital market.